I'm Only Human: A New E-road to Advancing Social Equity Through a Humanist Approach to Mentoring in Public Service. (June 2023) - Neal, Sue M.; Kline, Angela; Olejarski, Amanda M.; Gherardi, Michelle
This research reviews how mentoring has manifested in public service and how it can evolve to be better positioned to address key diversity, equity, and inclusion objectives. This work inventories the current understanding of public sector mentoring, highlighting the contrast between the classical mentoring approach of functionalism with the emerging humanist approach. Barriers to implementing meaningful humanist mentoring are reviewed, and e-mentoring is presented as a modality well situated to overcome these obstacles. The humanist e-mentoring model provides a process and modality to advance social equity by removing existing barriers to opportunities. Finally, best practices and outcomes for successfully implementing e-mentoring humanist and relationships in public service are presented and an updated model of critical outcomes is advanced. A brief agenda for future scholarship on this topic is presented.